The single resolution mechanism / Robby Houben, Werner Vandenbruwaene (eds.). - Houben, Robby; Vandenbruwaene, Werner (Privaat en publiek financieel recht, 2017)
On 1 January 2016 the Single Resolution Mechanism (SRM) became fully operational. The SRM creates a framework for the uniform resolution of banks in the euro area and after the Single Supervisory Mechanism (SSM), it is the second pillar of the European Banking Union. Whereas the SSM aims to reduce the risk of bank failure by unifying the supervision of banks, the SRM's aim is to increase the likelihood that a bank has been made "safe to fail", if it is likely to fail; and to reduce the risk of a government having to bail out a bank, if it actually fails. The key actor in the framework of the SRM is the Single Resolution Board (SRB). The SRB is the European agency responsible for the effective and consistent functioning of the SRM. This entails a responsibility for drawing up resolution plans and adopting decisions relating to resolution for the institutions that are within its realm. The actual execution of the adopted resolution scheme must be closely monitored by the SRB, but is carried out by the national resolution authorities (NRA). For institutions that fall outside the scope of the SRB's powers, the national resolution authorities are competent to adopt resolution plans and to take resolution decisions, albeit under oversight of the SRB. The SRB will be in charge of the Single Resolution Fund, a European pool of money that is transferred from domestic resolution funds, financed by the banking sector and set up to ensure that medium-term funding support is available while a credit institution is being restructured. This book takes stock after a year of application of the SRM and examines the situation from various perspectives: the perspective of the SRB, the NRA, the supervised bank and judicial protection. Special attention is given to the division of power between the SRB and the NRA and the impact on the supervised bank, the relationship and links between the SRM and the SSM and the query whether the right balance between national and supranational powers has been struck, also in view of the principle of subsidiarity. With contributions from Pierre E. Berger, Rudi Bonte, Evy De Batselier, Hans Gilliams, Stijn Goovaerts, Yves Herinckx, David Vanderstraeten and Eddy Wymeersch.